Innovative Cardiac Rehabilitation: Effects of Adaptive Postural Balance Exercise on Coronary Artery Disease and Type 2 Diabetes - Qin D; Liu G; Zhang J; Lin S; Liu X; Zhao J; Zhang Q; Ma M; Wang S (Diabetes, Metabolic Syndrome and Obesity)
Deyu Qin,1,2,* Guangxin Liu,2,* Jing Zhang,3 Shanshan Lin,4 Xinmeng Liu,2 Jingxiang Zhao,2 Qian Zhang,2 Mei Ma,2 Shusen Wang5 1The First Central Clinical School, Tianjin Medical University, Tianjin, 300070, People’s Republic of China; 2Department of Rehabilitation Medicine, Tianjin Chest Hospital, Tianjin, 300222, People’s Republic of China; 3Department of Endocrinology, Tianjin Chest Hospital, Tianjin, 300222, People’s Republic of China; 4Medical School, Nankai University, Tianjin, 300071, People’s Republic of China; 5Research Institute of Transplant Medicine, Organ Transplant Center, Tianjin First Central Hospital, School of Medicine, Nankai University, NHC Key Laboratory for Critical Care Medicine, Key Laboratory of Transplant Medicine, Chinese Academy of Medical Sciences, Tianjin, 300192, People’s Republic of China*These authors contributed equally to this workCorrespondence: Mei Ma, Email tjxkkfyxkm@126.com Shusen Wang, Email shusen@vip.163.comPurpose: This study aimed to evaluate the effects of Adaptive Postural Balance Cardiac Rehabilitation Exercise (APBCRE) on glycolipid metabolism and exercise endurance in patients with coronary artery disease (CAD) and type 2 diabetes mellitus (T2DM). Specifically, we compared the efficacy of APBCRE with aerobic exercise (AE) alone and irregular exercise (IE).Patients and Methods: This randomized controlled trial included 348 patients with CAD, comprising 261 patients with T2DM and 87 non-diabetic CAD patients as a control group. Participants were randomly assigned to one of four groups: the APBCRE group, the AE group, the IE group, or the non-diabetic AE control group. The intervention lasted 8 weeks, including a structured 6-week training phase. Metabolic markers and exercise endurance were assessed at baseline (week 1) and post-intervention (week 8). Cardiopulmonary exercise testing (CPET) was utilized to individualize exercise prescriptions and optimize intervention intensity.Results: The APBCRE group demonstrated significant improvements in fasting blood glucose (FBG) (− 11.34%, from 7.89 to 6.99 mmol/L, p < 0.05), HbA1c (− 8.87%, from 7.20% to 6.56%, p < 0.05), and LDL-C levels (− 12.21%, from 2.44 to 2.14 mmol/L, p < 0.05) compared to the AE and IE groups. While both APBCRE and AE improved lipid profiles, APBCRE demonstrated superior enhancements in exercise endurance, with max increasing by 18.71% (from 14.19 to 16.86 mL/min/kg, p < 0.05) and AT increasing by 16.00% (from 11.62 to 13.48 mL/min/kg, p < 0.05).Conclusion: These findings support the efficacy of APBCRE in improving glycolipid metabolism, exercise endurance, and neuromuscular coordination in patients with CAD and T2DM compared to AE alone.Keywords: type 2 diabetes mellitus, coronary artery disease, glycolipid metabolism, cardiopulmonary exercise testing